Pengaruh Motivasi, Keterampilan, dan Pengetahuan Berwirausaha terhadap Keberhasilan UMKM Muslimah Barefoot Entrepreneur di Kota Banjarmasin - Hastin Umi Anisah; Muhammad Zainal Abidin; Akhmad Supriyanto; Widyarfendhi Widyarfendhi (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2026)
This study aims to investigate the role of business motivation, entrepreneurial skills, and entrepreneurial knowledge in enhancing the business success of the muslimah barefoot entrepreneurs, MSMEs in Banjarmasin City. This research employs a quantitative method, which is a research method based on the positivist philosophy. It is used to study a specific population or sample, utilizes research instruments to collect data, involves quantitative/statistical data analysis, and aims to test predetermined hypotheses. This study uses a quantitative method with the variables of business motivation, entrepreneurial skills, entrepreneurial knowledge, and Business Success. The population of this research consists of all owners or managers of Barefoot Entrepreneur culinary businesses in Banjarmasin City. The sampling technique used in this study is purposive sampling, with a sample size of 43 respondents. Data were processed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS 4.0 software. The results of this study prove that: (1) Business motivation has a positive and significant effect on the business success of the muslimah barefoot entrepreneur MSMEs in Banjarmasin City; (2) Entrepreneurial skills have a positive and significant effect on the business success of the muslimah barefoot entrepreneur MSMEs in Banjarmasin City; and (3) Entrepreneurial knowledge has a positive and significant effect on the business success of the muslimah barefoot entrepreneurs, MSMEs in Banjarmasin City